In situ assays with tropical cladocerans to evaluate edge-of-field pesticide runoff toxicity - Lopes, Isabel
Tropical regions' economy is usually based on agriculture, which involves an intensive use, and even frequent overuse, of pesticides. Nevertheless, not much research has been done on the impact of pesticides on tropical aquatic ecosystems, which are often contaminated by runoff-related pesticide inputs due to unpredictable and torrential rainfalls. This study aimed to: (i) adapt and evaluate a short-term sublethal in situ assay using post-exposure feeding as an endpoint, to the tropical cladoceran species Diaphanosoma brachyurum (collected at the Pedra do Cavalo dam in the Paraguacu River basin, Bahia, Brazil), and, (ii) assess the role of the standard species Daphnia magna as an adequate laboratory surrogate. Lethal and sublethal (post-exposure feeding) responses were assessed for the two species. To evaluate these responses under environmentally realistic exposure conditions, a runoff event was simulated in an agricultural area previously contaminated with different deltamethrin concentrations. The resultant runoff water was used to set up microcosms with different dilutions, simulating the entrance of runoff water in an adjacent lentic system. An in situ assay with D. brachyurum was performed inside the microcosms, allowing to discriminate the effects due to deltamethrin from those due to other potential stressors associated with the experimental design (e.g. organism handling, load of suspended particles, microcosm design). Water samples were collected from microcosms to conduct a laboratory assay with D. magna. The in situ methodologies revealed to be suitable to conduct assays with D. brachyurum under tropical conditions, since all exposed organisms were successfully retrieved from the chambers. Furthermore, none of the potential stressors associated with the experimental design influenced the daphnids' performance. The tropical cladoceran species, exposed under more realistic conditions, revealed to be more sensitive than the laboratory standard species: lethal effects were only observed for D. brachyurum and sublethal effects were noticed at a lower deltamethrin concentration for this species than for D. magna. (c) 2006 Elsevier Ltd. All rights reserved.